ANALISIS PENGENDALIAN INTERN PENCAIRAN DANA HIBAH PEMERINTAH DAERAH KEPADA MASYARAKAT TAHUN ANGGARAN 2013 - Suryanto, Teguh; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the disbursement mechanism of local government grant to thecommunity. This grant is given with the regard of justice, compliance, rationality, and benefit principles for thecommunity. The research has been conducted on the Department of Revenue and Management of Surabaya Citywhich is located on Jalan Jimerto 25 â 27 Surabaya by using qualitative research which has been performed bycollecting, processing, and interpreting the data which has been obtained so it can give correct and completeinformation for the problems. The result of the research shows that the disbursement of grant is started from thetreasurer of expenditure submits the Request Payment Letter (SPP) and other documents to the FinancialAdministration Officials of Local Financial Management Working Unit (PPK-SKPKD). After it has beenobserved, the Financial Administration Officials of Local Financial Management Working Unit (PPK-SKPKD)makes the warrant of payment (SPM) and delegate the warrant of payment to the Local Financial ManagementOfficial (PPKD) to be authorized. Moreover, the Local Financial Management Official (PPKD) gives theWarrant of Payment (SPM) to the Power of Local Treasurer (Kuasa BUD) to be observed. Based on the Warrantof Payment (SPM), the Power of Local Treasurer (Kuasa BUD) makes the Warrant of Disbursement (SP2D)then gives it and other documents to the bank. Then, the bank disburses the fund to the third party.Keywords: Disbursement Mechanism of Local Government Grant, Grant, Local Government.